BUILDING LONG-LASTING CUSTOMER RELATIONSHIPS: THE INFLUENCE OF RELATIONSHIP MARKETING ON CUSTOMER LOYALTY IN THE SOLAR POWER INDUSTRY IN EKITI STATE, NIGERIA - Sadamoro, F; Ajayi, O. M; Ayodel , O. O; Areola , T. O (International Journal of Current Practice in Management and Leadership (IJCPML), 2022)
This study investigates the relationship between relationship marketing and customer loyalty in the solar power industry in Ekiti State, Nigeria. The solar power industry is a market with intense competition, and customers demand more than a competitive price from solar power companies. Thus, it is necessary for companies to offer quality products and services that will attract and retain customers. The aim of the study is to examine how relationship marketing strategies, such as commitment, trust, and complaint handling, influence customer loyalty in the solar power industry in Ekiti. The study uses a survey design and convenience sampling method to collect data from 150 households that use solar power services providers in Ekiti. The findings show that commitment, trust, and complaint handling all have a positive impact on customer loyalty in the solar power industry. The study underscores the importance of relationship marketing in maintaining customer loyalty in the energy industry, especially in developing countries like Nigeria, where the solar power industry is still in its nascent stage.